Cook Islands : Assessment of the Supervision and Regulation of the Financial Sector Volume II-Detailed Assessment of Observance of Standards and Codes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper focuses on key findings of the detailed assessment of observance of standards and codes in the financial sector of the Cook Islands (CI). The new legal framework in CI represents an important first step in correcting deficiencies, as they are all addressed in the new set of laws. The framework empowers the Financial Services Commission to license, supervise, and regulate the financial sector. It also provides it with enforcement authority in the event of noncompliance with the law, and to cooperate with foreign supervisors where necessary for implementation of comprehensive supervision on a consolidated basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet